IMAGE ANALYSIS METHODS – ANALYSIS OF MAMMOGRAPHIC IMAGE BASED ON TEXTURAL FEATURES - Lazarek, Jagoda (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
This paper presents an analysis of the possibility of using textural features for mammographic images classification. Textural features are calculated base on histogram, gradient matrix, run-length matrix, co-occurence matrix. Classification is based on k-NN classifier, the regions of interest can be classified as normal or abnormal. Results of some experiments are presented. All of abnormal regions were classified correctly